Evaluación del comportamiento de la cebolla de rama (allium fistulosum L.) en tres calibres y la desinfección con agua ozonificada con tres dosis en la poscosecha del campus Salache 2022-2023. - Vinocunga Chicaiza, María Fernanda (2023)
His research project was developed in the facilities from Cotopaxi Technical University, specifically in the farm house from Salache campus, in the laboratory from Agronomic Engineering degree. The research general aim was to assess the branch onion (Allium fistulosum L.) behavior into three calibers and the disinfection with ozonated water with three doses in the postharvest from Salache campus 2022-2023. It was applied a randomized complete block design with a 3x3 factorial arrangement, by giving 9 treatments and 27 experimental units total. The onion sizes under study were (1; 1.5; 2 cm), and the applied ozone doses (0; 0.3 and 0.06 ppm). The indicators to be assessed are physiopathies incidence, weight loss, firmness, pH and soluble solids. The calibers under study, which yielded positive results for 1.5cm into diameter, registering a 91.12% physiopathies incidence, a 1.1% weight loss, firmness 0.86, pH 5.73 and 8.67°. The applied dose gave the best result 0.6ppm, registering a 2.83% weight loss, firmness 0.73, pH 5.65 and 7.46° Brix, reaching optimal quality preservation for up to 22 days. at room temperature.